Work Activity and Subjectivity: A Behind-the-Scenes Look at the Work of Linemen - Brun, Jean-Pierre (Relations industrielles / Industrial Relations, 1995)
Using a study of linemen, this article shows how analyzing the subjective experience of linemen can enrich the understanding of work activities. The démonstration is based essentially on the phenomenon of defensive strategies, which allow human beings to maintain their psychic equilibrium despite the harmful effects of work organization. Finally, it is proposed that ergonomics should pay doser attention to the more personal phenomena that inevitably influence work activities.